Women Protection Policy in the Concept of Syibhul ‘iddah in Indonesian Marriage Law - Shofi, Muhammad; Mujiburohman, Mujiburohman (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
In general, the idah period is an obligation for women, not men. However, the Circular Letter of the Director General of Islamic Community Guidance Number P-005/DJ. III/HK.00.7/10/2021 concerning Marriage in the Period of Wife Idah contains a signal that men must also wait until the end of their ex-wife's Idah period, as if they are also subject to the same waiting period as women. This research aims to analyze the legal basis of these provisions through the perspective of the Compilation of Islamic Law (KHI) and the concept of man'i syar'i according to Wahbah Al-Zuhaili. This research is a type of normative legal research with a juridical approach. Legal materials are collected through the study of documents or literature, which are then analyzed in a qualitative descriptive manner. The most important legal material analyzed is the SE Director General of Islamic Guidance No. P-005/DJ. III/HK.00.7/10/2021, KHI, and Kitab Al-Fiqh al-Islami wa Adillatuhu. This research produced two main findings. First, the third point in the Circular Letter of the Director General of Islamic Guidance contains the concept of Syibhul ‘iddah (similar to idah) which is rooted in the Compilation of Islamic Law (KHI), especially Articles 41 and 42. These articles regulate the prohibition of marrying a woman who has a marriage cord during the idah period, including the obligation to wait for a husband who has divorced his fourth wife. This concept is also in line with Wahbah al-Zuhaili's view on man'i syar'i (syar'i obstacle). However, in contrast to KHI and the opinion of Wahbah al-Zuhaili which only limits marriage to certain women, this Circular Letter prohibits the ex-husband from marrying any woman during the period of idah of his ex-wife. Second, this Circular Letter fills the void of administrative law, because previously there was no rule limiting the registration of marriages during the wife's idah period. Thus, this Circular Letter becomes a bridge between the provisions of classical fiqh and modern administrative needs, and can be understood as a form of administrative ijtihad in responding to contemporary legal needs.